1969
DOI: 10.1039/j39690002030
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the syntheses of heterocyclic compounds. Part CCC. Syntheses of salutaridine, sinoacutine, and thebaine. Formal total syntheses of morphine and sinomenine

Abstract: The diazotisation of (*)-I -(2-amino-3-benzyloxy-4-methoxybenzyl) -1,2,3,4-tetrahydro-6,7-dimethoxy-2methylisoquinoline (VIII) followed by the thermal decomposition of the resulting diazoniurn salt, gave ( f ) -salutaridine (11) [or (f)-sinoacutine], which was converted into (*)-thebaine (111). The 2-aminobenzylisoquinoline (VIII) was resolved, and the (-)and (+) -enantiomers (VIIIa and b) were used for the syntheses of salutaridine (IIa), sinoacutine (IIb), and thebaine (IIIa) and its antipode (IIIb). This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Positive Cotton effect at 300 nm and negative Cotton effect at 340 nm confirmed that the absolute configuration of subunit 'c' was same as that of 8. 16 Consequently, the structure of 2 was fully established, and named as sallisonine B.…”
Section: Resultsmentioning
confidence: 99%
“…Positive Cotton effect at 300 nm and negative Cotton effect at 340 nm confirmed that the absolute configuration of subunit 'c' was same as that of 8. 16 Consequently, the structure of 2 was fully established, and named as sallisonine B.…”
Section: Resultsmentioning
confidence: 99%
“…Representative morphine alkaloids are morphine (200), codeine (201), thebaine (202), salutaridine (203), pallidine (204), flavinantine (205), and sinomenine (206). The structures of these alkaloids were elucidated by a combination of Hofmann degradation and IR, UV, NMR, and mass spectroscopies.…”
Section: Morphine and Related Alkaloidsmentioning
confidence: 99%
“…Total synthesis of morphine (200) was achieved first by Gates [197] and then by Ginsburg [198]. It has also been prepared by Barton and his associates [199] with biogenetictype sequences.…”
Section: Morphine and Related Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations